PERTANGGUNGJAWABAN PIDANA TERHADAP PEMILIK WEBSITE YANG MENGANDUNG MUATAN PORNOGRAFI - Agus Permata Giri, I Putu; Putra Ariana, I Gede (Kertha Wicara : Journal Ilmu Hukum, 2014)
This paper entitled "Criminal Responsibility of the Website with PornographyContent's Owner" . The research method used in this paper is a normative analysis. Oneof the most famous and troubling type of cybercrime due to its rapid spread, enormousdangers and bad impacts to the society is the cybercrime in terms of morality, Cybersexis. One of the several types of the cybersex is the network sites that contain adult materialsuch as pornography that could break children’s morality, it is caused due to easy accessto those sites that allow it to be accessed by anyone at anytime. Therefore the problem ofcriminal Responsibility of the owner’s of the porn websites is very important in order tocreate a deterrent effect for them. People who own a pornographic website can becharged with the provisions of Act no. 44 Year 2008 on Pornography, and the Act no. 11Year 2008 on Information and Electronic Transactions. Criminal sanction are in the formof imprisonment and / or criminal penalties that apply cumulatively - alternative.
Keywords: Cyber Crime, Cybersex, Pornography, Criminal Responsibility